Temple Beth Israel Celebrates Cantor Michael Loring's 80th Birthday - Watkins, Howard::::::::: (1988)
Cantor Michael Loring at microphone; ? removing the Torah from the Holy Ark; ? Opening curtain, Rabbi Ken Segel, and William Leifer;